Atriplex canescens: A new host for Cistanche deserticola. Issue 6 (June 2021) - Wang, Fangming; Zhuo, Bingyu; Wang, Shuai; Lou, Jin; Zhang, Yuan; Chen, Qingliang; Shi, Ziyi; Song, Yuelin; Tu, Pengfei
Abstract: Cistanche deserticola has been historically used in traditional Chinese medicine for supplementing kidney (yang) function, benefiting blood and essence, and moistening intestines in order to pass stool. Its host, Haloxylon ammodendron, is an important pioneer plant used for windbreaks and sand dune fixation, which are strategies used for the control desertification. For a long time, it has been considered that C. deserticola can only parasitize H. ammodendron . In this study, morphological identification, gene barcoding identification and inoculation experiment were carried out, we finally found that C. deserticola can also parasitize Atriplex canescens. A. canescens is a species of Chenopodiaceae with a wide range of adaptability. Compared with H. ammodendron, it has more biomass and a wider range of ecological adaptability, making it more suitable for the industrial production of C. deserticola . In addition, we also found that the concentration of active components was higher in C. deserticola parasitized on A. canescens than in those parasitized on H. ammodendron ; this finding further suggests that the application of C. deserticola on a larger scale warrants further exploration. Abstract : Cistanche deserticola, parasitism, DNA barcode-based identification, traditional Chinese medicine, Cistanche salsa